Application of Improved Genetic Algorithm in PID Controller Parameters Optimization - Ying Chen; Yong-jie Ma; Wen-xia Yun (Institute of Advanced Engineering and Science, 2013)
The setting and optimization of Proportion Integration Differentiation(PID) parameters have been always the important study topics in the automatic control field. The current optimization design methods are often difficult to consider the system requirements for quickness ,reliability and robustness .So a method of PID controller parameters optimization based on Improved Genetic Algorithm(IGA) is presented .Simulations with Matlab have proved that the control performance index based on IGA is better than that of the GA method and Z-N method, and is a method which has good practical value of the PID parameter setting and optimization.DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2301